COVID-19 in Bangladesh: Wave-centric assessments and mitigation measures for future pandemics - Tahani Tabassum; Maisha Farzana; Abida Nurun Nahar; Yusha Araf; Md Asad Ullah; Tanjim Ishraq Rahaman; Nairita Ahsan Faruqui; Md Nazmul Islam Prottoy; Saeed Anwar; Nurshad Ali; Mohammad Jakir Hosen (Heliyon, 2023)
The ongoing pandemic COVID-19 caused by Severe Acute Respiratory Coronavirus-2 (SARS-CoV-2) has wreaked havoc globally by affecting millions of lives. Although different countries found the implementation of emergency measures useful to combat the viral pandemic, many countries are still experiencing the resurgence of COVID-19 cases with new variants even after following strict containment guidelines. Country-specific lessons learned from the ongoing COVID-19 pandemic can be utilized in commencing a successful battle against the potential future outbreaks. In this article, we analyzed the overall scenario of the COVID-19 pandemic in Bangladesh from Alpha to Omicron variant and discussed the demographic, political, economic, social, and environmental influences on the mitigation strategies employed by the country to combat the pandemic. We also tried to explore the preparedness and precautionary measures taken by the responsible authorities, the choice of strategies implemented, and the effectiveness of the response initiated by the government and relevant agencies. Finally, we discussed the possible strategies that might help Bangladesh to combat future COVID-19 waves and other possible pandemics based on the experiences gathered from the ongoing COVID-19 pandemic.